Model-Model Pembelajaran Pendidikan Agama Islam - Srihartini, Yusi; Gagan; Latipatinupus; Maenatul M, Rina (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to explore Islamic Religious Education (PAI) learning models that can improve students' cognitive, affective, and psychomotor intelligence. The background of the research underscores the importance of various elements in education, such as teachers, students, curriculum, environment, and chosen learning model. The learning model, as a teaching plan, must be adapted to the needs of students and be able to cover theoretical and practical aspects. Success in learning depends heavily on the selection of the right model, which influences five key aspects of effective learning: clarity, variety, task orientation, student engagement, and achieving high success. This study formulates several main problems, including the types of PAI learning models, aspects that affect students' intelligence, and models that can improve cognitive, affective, and psychomotor intelligence. The focus is also given on the Contextual Teaching and Learning (CTL) approach and life skills. The findings of this study are expected to contribute to the development of effective learning strategies for Islamic religious education.